1970
DOI: 10.1002/aja.1001270104
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing villus size in the small intestine of adult rats as revealed by transposition of intestinal segments

Abstract: As an index of villus size, the number of epithelial cells per representative villus section was counted in longitudinal sections of the rat small intestine. Villus size was found to decrease gradually along the length of the small intestine, with villi being nearly three times as large in upper duodenum as in terminal ileum. The influence of various surgical operations on villus size was then examined. In ileal segments inserted into the jejunum, villi enlarged to the size of local jejunal villi. In jejunal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
84
0
4

Year Published

1971
1971
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(96 citation statements)
references
References 12 publications
8
84
0
4
Order By: Relevance
“…Although in the rat the villus number increased after intestinal resection (Bochkov, 1959), intestinal villi of chickens tested in this study adapt to activated intestinal absorptive function not by increasing their numbers but by fusing together into larger villi. In rats, in addition to villus hyperplasia after transposition of the ileum to the jejunal location (Dowling and Booth, 1967;Altmann and Leblond, 1970;Wang et al, 1998), hypertrophy of microvilli and lateral cell membranes was also reported after midgut resection (Tilson and Wright, 1971a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the rat the villus number increased after intestinal resection (Bochkov, 1959), intestinal villi of chickens tested in this study adapt to activated intestinal absorptive function not by increasing their numbers but by fusing together into larger villi. In rats, in addition to villus hyperplasia after transposition of the ileum to the jejunal location (Dowling and Booth, 1967;Altmann and Leblond, 1970;Wang et al, 1998), hypertrophy of microvilli and lateral cell membranes was also reported after midgut resection (Tilson and Wright, 1971a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, intestinal villi in intact chickens gradually decrease in length (Rolls et al, 1978) and size (Altmann and Leblond, 1970) moving from the duodenum to the ileum. Lower villus height (Khambualai et al, 2009) and narrower cell area (Incharoen and Yamauchi, 2009) were observed in the ileum compared with the jejunum.…”
mentioning
confidence: 98%
“…Altmann investigated the effects of luminal pancreatic juice and bile on the growth of small intestinal mucosa in rats; it was reported that pancreatic juice and bile had trophic effect on the intestinal mucosa (Altmann and Leblond 1970;Altmann 1972). In their model, a duodenal segment including the pancreatic duct was anastomosed to the ileum.…”
Section: Discussion Evaluation Of the Experimental Modelmentioning
confidence: 99%
“…pancreatic juice diversion; enteroglucagon; intestinal mucosal growth; pancreaticoileostomy It was previously reported that intestinal pancreatic juice plays an important role in intestinal adaptation (bowling 1982), and that pancreatic juice has a trophic effect on the small intestinal mucosa (Altmann and Leblond 1970;Altmann 1972). However, others have suggested that it is still controversial whether pancreatic juice has a trophic effect on intestinal mucosa (Miazza et al 1982).…”
mentioning
confidence: 99%
“…These findings suggest that the proliferative effects of fat are not associated with the adequacy of the energy supply. Orally administered fat is known to increase exocrine pancreaticc juice and bile (12) and to promote the release of neurotensin (13,14). These mechanisms may be related to the trophic effects of the 4% FED on the intestine (15).…”
Section: Discussionmentioning
confidence: 99%